2016
DOI: 10.1016/j.lithos.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Sub-seafloor epidosite alteration: Timing, depth and stratigraphic distribution in the Semail ophiolite, Oman

Abstract: Pervasive epidotization of igneous rocks is a common feature in the ophiolite record of hydrothermally altered oceanic crust. Current genetic models view epidosites as markers of focussed upflow of hydrothermal fluid beneath oceanic spreading ridges. The epidosites are envisaged to form at the base of the sheeted dike complex (SDC) during active plate spreading. Our mapping of the Semail ophiolite in Oman has revealed abundant epidosites in the volcanic sequence, some exceeding 1 km 2 in extent.They are more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(95 citation statements)
references
References 46 publications
(38 reference statements)
5
89
1
Order By: Relevance
“…It was collected from the base of the sheeted dike complex in the Wadi Amadhi, just 79 m above the isotropic gabbros (i.e., former melt lens). The sample is a monomineralic epidote precipitate and not equivalent to epidosites that have been observed in the sheeted dikes of the northern Oman Ophiolite (Gilgen et al, ; Nehlig et al, ). The average fluid inclusion entrapment temperature of 330 °C and the seawater‐like salinities of the fluid inclusions are similar to results of earlier workers.…”
Section: Discussionmentioning
confidence: 91%
“…It was collected from the base of the sheeted dike complex in the Wadi Amadhi, just 79 m above the isotropic gabbros (i.e., former melt lens). The sample is a monomineralic epidote precipitate and not equivalent to epidosites that have been observed in the sheeted dikes of the northern Oman Ophiolite (Gilgen et al, ; Nehlig et al, ). The average fluid inclusion entrapment temperature of 330 °C and the seawater‐like salinities of the fluid inclusions are similar to results of earlier workers.…”
Section: Discussionmentioning
confidence: 91%
“…Variations in volcanostratigraphy can then be used to test previously proposed along-strike variations in subduction-zone influence (e.g. Goodenough et al, 2010;Python et al, 2008) and hydrothermal processes (Alabaster et al, 1982;Gilgen et al, 2016;MacLeod and Rothery, 1992), as well as the overall significance of the "Phase 2" magmatic Nicolas et al (2000) with the additional differentiation of the structurally separate western (W.) and eastern (E.) Fizh blocks, showing the area mapped in this study. Inset: map of Tethyan ophiolites adapted after Dilek et al (2007) with U-Pb zircon ages of initial accretion indicated for the Albian-Turonian ophiolite chain of 1 Troodos, 2 Kizildag, 3 Nain, 4 Deshir, and 5 Semail after Shafaii Moghadam et al (2013) and references therein.…”
mentioning
confidence: 89%
“…4a). Gilgen et al (2016) sampled similar lavas and their dyke equivalents (pillow lava sample RAM010 was remeasured with ICP-MS for this study), assigning them to Lasail on the basis of their clinopyroxene compositions. also reported similar lavas within a lens of "Axial Lasail" intercalated within Geotimes near Wadi Hawarim.…”
Section: Interpretation Of Depleted Lasail Compositionsmentioning
confidence: 99%
See 2 more Smart Citations